The incorporation of computer-aided learning (CAL) material for medicinal chemistry teaching in the infectious disease and pharmacotherapeutics subject / Siti Marziah Abd Ghapar - Abd Ghapar, Siti Marziah (2013)
How long Medicinal Chemistry subject has been taught in Faculty of Pharmacy of UiTM? And how hard the lecturers and also the students tried to give their best in increase understanding in Medicinal Chemistry subject? It seems like we will never get the solutions for the problems with less understanding towards Medicinal Chemistry subjects among students if the method of teaching these subjects remain forever. Computer Aided Learning (CAL) program is the best solution for this problem. It is a presentation of Medicinal Chemistry in more attractive, full of information, simplest way and in convenience manner of delivering these subjects to the students. CAL program was developed in a video form, and the content is adopted from second year subject, which is Medicinal Chemistry of Infectious Diseases and Pharmacotherapeutics. An entry survey was conducted before the trial of the program by the students, and it was found that students have the interest in learning Medicinal Chemistry subject but difficult for them to understand and memorize it. The students were asked to use the program and answer some questions in a trial session that was conducted in Computer Laboratory 2, Level 5 of FF2. Upon completion of the trial session, they had filled in the exit survey form, and from this form, an evaluation has been made to identify whether this program is suitable or not to be implemented in the current teaching methodology of Medicinal Chemistry subjects. The result is yes!